The Effect of Adherence on The Quality of Life in Pulmonary Tuberculosis Patients with or without Comorbidities - Annisa Rosita Hafiizh; Abdul Rahem; Yuni Priyandani (Faculty of Medicine Universitas Sebelas Maret, 2025)
Introduction: Pulmonary tuberculosis (TB) cases in East Jawa increased sharply by 73.3% in 2022, with Surabaya among the highest contributors. Nearly half of TB patients have comorbidities, which complicate therapy and may reduce medication adherence. Non-adherence to anti-tuberculosis drugs (OAT) can decrease treatment success and quality of life (QoL). This study aims to analyze the effect between OAT adherence and QoL in pulmonary TB patients with and without comorbidities.Methods: This cross-sectional analytic study was conducted at Pegirian Surabaya Health Center and Husada Prima Surabaya Hospital from September to December 2024. Seventy-two respondents were recruited and evenly divided into two groups, with thirty-six patients in each group. Adherence was measure using 5-Tepat Questionnaire and QoL was assessed using AqoL-4D instrument. Data were analyzed with Chi-Square and Mann-Whitney tests.Results: Among TB patients without comorbidities, 75% were adherent to OAT, compared to 61.1% in the group with comorbidities. There was no statistically significant difference in adherence rates between groups (p = 0.206). However, patients without comorbidities who were adherent had a significantly higher median quality of life score of 92.00 (p = 0.001), while adherent patients with comorbidities had a median score of 78.00 (p = 0.000).Conclusion: Adherence OAT treatment significantly improves the quality of life of pulmonary TB patients, particularly among those with comorbidities. These findings underscore the importance of interventions to enhance adherence as part of comprehensive TB management strategies.